2014
DOI: 10.1017/s0029665113003935
|View full text |Cite
|
Sign up to set email alerts
|

The potential for dietary factors to prevent or treat osteoarthritis

Abstract: Osteoarthritis (OA) is a degenerative joint disease for which there are no disease-modifying drugs. It is a leading cause of disability in the UK. Increasing age and obesity are both major risk factors for OA and the health and economic burden of this disease will increase in the future. Focusing on compounds from the habitual diet that may prevent the onset or slow the progression of OA is a strategy that has been under-investigated to date. An approach that relies on dietary modification is clearly attractiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 162 publications
1
29
0
1
Order By: Relevance
“…Severe OA might also require surgical interventions such as knee or hip arthroplasty [9]. Dietary factors or supplements have been discussed as options in the management or prevention of OA [10]. …”
Section: Introductionmentioning
confidence: 99%
“…Severe OA might also require surgical interventions such as knee or hip arthroplasty [9]. Dietary factors or supplements have been discussed as options in the management or prevention of OA [10]. …”
Section: Introductionmentioning
confidence: 99%
“…One area of research has focused specifically on nutrient deficiencies. A recent review article reported that a 5-year longitudinal study found an association between vitamin D and pain (5), specifically that moderate vitamin D deficiency predicted both knee and hip pain as measured by vitamin D serum levels (25-hydroxyvitamin D). Additionally, a questionnaire-based study also found an association between vitamin D and pain where experimental pain and self-reported measures among subjects with lower serum levels of vitamin D were associated with greater clinical pain, especially for African Americans compared to Caucasians (6).…”
Section: Introductionmentioning
confidence: 99%
“…One pilot study on diet elucidated that low intake of vitamins C and D are the most significant risk factors of OA (10). However, studies examining vitamin D intake and osteoarthritis pain reveal conflicting results, with some studies demonstrating minor to no benefit for pain outcomes (5, 8, 11). For example, a study examining 36,282 participants from the Women’s Health Initiative randomized trial found vitamin D did not have an association with the frequency or severity of joint symptoms (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Naime, epidemiološka istraživanja su suboptimalni unos pojedinih nutrijenata povezale sa rizikom za nastanak i razvoj OA (8). Posebno značajan nutritivni aspekt predstavlja racionalna i bezbedna primena sve većeg broja dijetetskih suplemenata u primarnoj i sekundarnoj prevenciji OA (9).…”
Section: Uvodunclassified